2018
DOI: 10.21037/jtd.2018.07.46
|View full text |Cite
|
Sign up to set email alerts
|

Application value of the NoSAS score for screening sleep-disordered breathing

Abstract: The NoSAS score and the Berlin questionnaire both exhibited good predictive value for SDB patients. NoSAS is a more suitable questionnaire to use in clinic for the conveniences but the similar performance with another questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Our study, performed in a population from a sleep clinic, yielded an obvious lower AUC of the NoSAS score than a previous study [18] which included Caucasians and was also carried out in a sleep clinic (0.715 vs. 0.770 for all SDB; 0.697 vs. 0.746 for moderate-to-severe SDB). Similar results were also observed that AUCs of the NoSAS score in the Asian populations [10][11][12] were lower than in the Caucasian populations [9,16,17]. ese may be partially explained by the difference in the pathogenesis of SDB between Asians and Caucasians.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our study, performed in a population from a sleep clinic, yielded an obvious lower AUC of the NoSAS score than a previous study [18] which included Caucasians and was also carried out in a sleep clinic (0.715 vs. 0.770 for all SDB; 0.697 vs. 0.746 for moderate-to-severe SDB). Similar results were also observed that AUCs of the NoSAS score in the Asian populations [10][11][12] were lower than in the Caucasian populations [9,16,17]. ese may be partially explained by the difference in the pathogenesis of SDB between Asians and Caucasians.…”
Section: Discussionsupporting
confidence: 76%
“…e AUCs of the NoSAS score reached as high as 0.81 in the EPISONO cohort and 0.748 in the Asian population while the AUCs of STOP-Bang were almost around 0.7. When applied in hospital-based populations [11,12], the NoSAS score had equivalent or higher performance than the other tools including STOP-Bang questionnaire, ESS, and Berlin scores. Additionally, the NoSAS score was shown to be effective in predicting SDB in patients with depressive majors [16] or with insomnia [17].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The fact that the NoSAS score consist of objective parameters may also have played a role in having a higher specificity than the other questionnaires in our population. Additionally, containing any subjective parameter except for snoring makes the NoSAS score more convenient for clinicians to use [20].…”
Section: Discussionmentioning
confidence: 99%
“…17 Afterwards, this score was also validated in different settings, reporting adequate performance as screening model for OSA: in a multiethnic Asian cohort, in a hospital-based sample, in depressive subjects, and in a sleep clinic. [18][19][20][21][22] The No-Apnea 23 tool is a newly developed and validated screening instrument that includes only two objective parameters: neck circumference (NC) and age, with a total score ranging from 0 to 9 (cutoff point ≥3 classifies patients at high risk for OSA). In derivation and validation cohorts, No-Apnea showed adequate performance in OSA screening, with a discriminatory ability that was similar and indistinguishable from the performance of either STOP-Bang or NoSAS.…”
Section: Introductionmentioning
confidence: 99%